Soil Properties and Macrofauna Community in a Converted Intensive Rice Field into an Organic Polyculture in Malang Regency, Indonesia: Soil Properties and Macrofauna Community in a Converted Intensive Rice Field - Inayah, Durrotul; Mustafa, Irfan; Arisoesilaningsih, Endang (Journal of Tropical Life Science, 2024)
Farmers in Malang cultivated rice intensively since 2019 due to water availability but reduce yields. It might also reduce soil productivity and increase pest attacks, so the conversion field to organic polyculture was needed using sorghum and legumes. The research aims were to evaluate soil fauna dynamics and soil properties in the three, six, and 12 months after converting (mac) into organic polyculture. Soil and micro-climate factors were recorded including air temperature (°C), day length (hours), rainfall (mm), water content (%), organic matter content (%), electrical conductivity (mS.m-1), pH, and soil bulk density (g.cm-3). Soil macrofauna was sampled using hand sorting (20 x 20 x 10 cm) with five plots at each field. Identified soil macrofauna was used to determine the density, frequency, Important Value Index (IVI), Shannon-Wiener Diversity Index (H'), Evenness Index (E), Simpson Dominance Index (D), Diversity t-test, and Indicator Species. The Canonical Correspondence Analysis (CCA) was used to analyze the interaction among abiotic factors and macrofauna using PAST 4.05. Results showed that the improvement of soil properties including soil organic matter and soil macrofauna was recorded at 6 mac compared to the intensive rice field, and continuously at 12 mac. The richness, diversity, and evenness of soil macrofauna taxa were higher in the converted field than in the intensive one due to organic polyculture. Moreover, we recorded a better proportion of detritivores and predators in the converted field after 12 months. Based on Indicator Species analysis, the dominant fire ants (Solenopsis sp.) in the intensive rice field might be considered as a potential indicator of unhealthy soil in the intensive rice fields. Whereas in the converted field the dominancy of these ants greatly decreased. We concluded that within 6 months conversion using the organic polyculture improved soil properties.